Bandits - Yenen, Alp (2024)
Abstract: In the legal sense, the transgression of banditry is rooted in the act of robbery, which involves the unlawful appropriation of property through the use or the threat of violence. The bandit’s robbery can be portrayed as a challenge to the prevailing distribution of material goods and the socioeconomic concept of justice, especially when there is a perception of asymmetric power relations in society as a structural problem. While the state authorities in particular may attempt to label the bandits as criminals – or even terrorists – and thus deheroize them, the popular heroization of bandits is based on their struggle for the violent reversal of an unjust distribution of wealth that primarily benefits the authorities. Hence, in the heroization of banditry, a violent transgression of the normative order is contextually linked to a desired reversal of the socioeconomic order of justice, positioning bandits as ambiguous figures in the typological field of the heroic. By exploring the adoration of a bandit as a social hero or, conversely, the marking of the same actor as a criminal perpetrator, conclusions can be drawn about the competing social actors in the field of power